Sistem Pendukung Keputusan Penilaian Kinerja Guru untuk Rekomendasi Guru Tetap Berbasis Balanced Scorecard dengan Pendekatan Analytic Network Process - Marimin Marimin; Zaqi Kurniawan; Rusdah Rusdah (Ikatan Ahli Informatika Indonesia, 2019)
Teacher Performance Assessment guarantees a quality learning process at all levels of education. Educational supervision will be carried out with the aim to improve the quality of teaching / teacher so that the competitiveness of students studying at the school will increase towards a better direction. Supervision assessment is a class visit technique to obtain data about the actual situation regarding the ability and skills of teachers in teaching and mastery of class. To determine the teacher's performance, one approach can be done using the Balanced Source card. The determination of teacher performance is then processed using Analytic Network Process-based modeling to improve teacher evaluation criteria that are still low. With the help of Super Decision software, a decision support system was created in determining teacher performance. The results of this study are the recommendations of permanent teachers in Junior High Schools, High Schools, Vocational Schools Yadika 12 Depok based on performance to be objective and make more efficient decisions.